Catalytic Activity of Porous Phosphate Heterostructures-Fe towards Reactive Black 5 Degradation - Marco S. Lucas; Manuel Algarra; José Jiménez-Jiménez; Enrique Rodríguez-Castellón; José A. Peres (International Journal of Photoenergy)
Fenton’s reaction is often used to decompose stable substances in wastewater. In this study, experiments based on the effect of porous phosphate heterostructures as catalyst sorbent of Fe2+ synthesised by different procedures were planned. The examined PPH-Fe/H2O2 as oxidant in a heterogeneous process under mild conditions at pH 5 was found to be very efficient for discoloration of a simulated wastewater containing 50 mg L−1 of a commercial azo dye (Reactive Black 5) reaching 95% of decolourization. Under the described conditions total visual decolourization was achieved after 360 min. This study can provide a simple, effective, and economic system ideal for the treatment of toxic and nonbiodegradable azo dyes.